Growth Hormone Therapy Benefits Pituitary Stalk Interruption Syndrome Patients with Short Stature: A Retrospective Study of 75 Han Chinese - Cheng-Zhi Wang; Ling-Ling Guo; Bai-Yu Han; An-Ping Wang; Hong-Yan Liu; Xing Su; Qing-Hua Guo; Yi-Ming Mu (International Journal of Endocrinology)
Objective. We aim to investigate the long-term benefits of growth hormone (GH) therapy in short stature adolescents and adults with pituitary stalk interruption syndrome (PSIS), which would be beneficial for future clinical applications. Design and Methods. In this study, initial height, final height, total height gain, and GH treatment history were retrospectively investigated in 75 Chinese PSIS patients. We compared height gain between the GH treated cohort and untreated cohort and explored the impact of different GH therapy duration on height gain. Results. For GH treated patients, their final height (SDS) increased from -1.99±1.91 (−6.93~2.80) at bone age (BA) of 11.2 (5.0~17.0) years to -1.47±1.64 (−7.82~1.05) at BA of 16.6 (8.0~18.0) years (P=0.016). And GH treated patients had more height gain than the untreated patients (P<0.05). There was a significant difference between the different GH therapy duration groups (P=0.001): GH 0 versus GH 3, P=0.000; GH 1 versus GH 3, P=0.028; GH 2 versus GH 3, P=0.044. Conclusion. Adult Chinese PSIS patients with short stature benefited the most from at least 12 months of GH therapy. Although patient diagnosis age was lagged behind in the developing countries, GH treatment was still effective for them and resulted in a higher final height and more height gain.